Evaluation of two sorghum (Sorghum bicolor (L.)Moench) stover varieties as sole roughage source for dairy cattle - and RM Sundaram, S B N Rao et al. (Indian Journal of Dairy Science, 2025)
The present experiment was conducted to evaluate two popular sorghum stover varieties grown in parts of Karnataka and Maharashtra. The varieties are M35-1 (very old popular rabi jowar released for dry regions of Maharashtra) and PVK-1009 (Kharif Sorghum released for Maharashtra having more minerals). They have been subjected for chemical composition and in vitro studies using standard procedures.   M35-1 has significantly higher CP (P